The evolution of recommendations for cranberry use in recurrent urinary tract infections: A systematic review - N.I. Carvalho; G.G. Leite; B.B. Silva; I.L. Souza; L.D. Souza; I.M. De Faria (Український Журнал Нефрології та Діалізу, 2021)
Abstract. Urinary tract infections (UTI) constitute a major complaint in medical offices worldwide, especially concerning women. Although the efficacy of cranberry in UTI prevention is still controversial it has long been recommended for use in clinical practice. Based on the recommendation evaluation, the present study aimed to conduct a systematic review to assess the efficacy of cranberry prophylaxis in recurrent UTIs in women. Main changes among reviewed publications revolved around the mechanism by which cranberry produce the results observed and once it was established that it relates to bacterial fimbriae-mediated adhesion, most authors now struggle to establish accurate measures to come up with a protocol for its use. Many studies compared cranberry effects to placebo and traditional antibiotic treatment and showed promising results about effectiveness, as well as economic drawbacks. Altogether, cranberries could help to delay ecological resistance to antibiotics as well as protect patients from infections. Further investigation, mainly regarding dosage, is needed to formulate protocols and safely introduce cranberries to clinical practice